Hubungan Pengelolaan Emosi Dan Sosialisasi Dalam Keluarga Dengan Kepatuhan Norma Kesopanan Siswa Smp - Andum Akuri; Edy Suyanto; Shinta Julianti (Jurnal Neo Societal, 2026)
This study explains the relationship between emotion management and family socialization with students' compliance with politeness norms at SMP Negeri 1 Purwokerto. The issue is important because polite behavior reflects the quality of social interaction between students, teachers, and peers. A quantitative approach with an explanatory survey method was used. The population consisted of 504 seventh- and eighth-grade students, and 223 students were selected through proportionate stratified random sampling. Data were collected using a questionnaire and analyzed through validity testing, reliability testing, and Spearman correlation. The results show that emotion management has a positive and significant relationship with students' compliance with politeness norms, with a correlation coefficient of 0.229 and a significance value of 0.001. Family socialization also has a positive and significant relationship with students' compliance with politeness norms, with a coefficient of 0.389 and a significance value of 0.000. These findings indicate that polite behavior is shaped by internal emotional control and value internalization within the family